Financial Development and Unemployment in OECD Countries: Evidence from Pre- and Post-Pandemic Periods - Yan, Zhang; Mohd Radzi, Naziatul Aziah; Saidi, Normaizatul Akma (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2026)
Research Originality: This study systematically analyzed the relationship between financial development and the unemployment rate using data from 38 OECD countries from 2000 to 2024. It not only examines differences across income levels but also deeply investigates the impact of the COVID-19 pandemic, thereby overcoming the limitations of previous studies that relied on alternative indicators of economic growth. Research Objectives: The purpose of this study is to assess whether a robust financial market can reduce unemployment rates, as well as how this effect changes under different economic backgrounds. Research Method: This study, using panel data from the World Bank and the OECD for the period 2000 to 2024, employs the fixed-effects model to test the direct impact of financial development level and the moderating effect of the epidemic. Empirical Results: The pandemic has weakened the effect of financial development on reducing the unemployment rate by optimizing capital allocation, but fiscal stimulus measures have boosted economic recovery. Therefore, even after excluding the data from the crisis period, the research findings remain robust. Implications: High-income countries must focus on improving the efficiency of fiscal resource allocation while maintaining labor-market stability. In contrast, middle- and high-income countries need to support the development of manufacturing and small and medium-sized enterprises while reducing financial instability risks, especially during times of crisis. JEL Classification: E24, G20, O40